The impact of artificial intelligence on sustainable development performance of public healthcare supply chain-an empirical study based on listed Chinese pharmaceutical companies - Chen, Qianlan; Long, Ping; Dong, Ruihai; Li, Chaoling; Mao, Siyi (Frontiers in Public Health, 2025)
With the continuous deepening of the digital transformation of the public healthcare supply chain, as the next step of digitalization, intelligent transformation has received much attention, especially how artificial intelligence can improve the sustainable development performance of the supply chain needs to be studied. In order to fill this gap, this paper establishes a research model of artificial intelligence, green supply chain management practice, industry competition and sustainable development performance of public healthcare supply chain. Taking Chinese listed pharmaceutical enterprises as research objects, this paper conducts empirical analysis on 301 valid questionnaires through questionnaire survey and structural equation model. The relationship between artificial intelligence, green supply chain management practice, industry competition and sustainable development performance of public healthcare supply chain is studied. In this paper, green supply chain management practice is regarded as the intermediary variable, industry competition is regarded as the moderating variable, and a research model with both mediation and regulation is constructed. The empirical results show that: (1) Artificial intelligence has a significant positive impact on the sustainable development performance of public healthcare supply chain; (2) Artificial intelligence has a positive impact on green supply chain management practice; (3) Green supply chain management practice has a positive impact on the sustainable development performance of public healthcare supply chain; (4) Green supply chain management practices play an intermediary role in the effect of artificial intelligence on the sustainable development performance of public healthcare supply chain, that is, artificial intelligence improves the sustainable development performance of supply chain through green supply chain management practices; (5) Industry competition actively regulates the impact of artificial intelligence on the sustainable development performance of public healthcare supply chain. This study enriches the literature on AI and public healthcare supply chains, while providing new practice guidelines for sustainable development and modern management of public healthcare supply chains.